Censorship in Flux: Sex and Sexological Knowledge at the Great Police Exhibition of 1926 in Weimar Germany - Lang, Birgit (Journal of the history of sexuality, 2024)
Lang examines multiple sites and directions of regulatory and policing practices in 1920s Germany. She uses the example of the Great Police Exhibition (1926), which took place during the establishment of a new democratic regime. While the protection of youth was at the center of both authoritarian and democratic censorship regimes in Germany, the democratic authorities' quest for acceptance translated into their public recognition of the historical relativism of what constituted sexual offense and openness about current censorship practices. Drawing on an array of sexological materials designed with the assistance of sexologists, the exhibition presented a teleological history of German censorship, a progression from punitive censorship during the authoritarian Wilhelmine era toward censorship as a form of sexual pedagogy in the democratic Weimar Republic.